2021
DOI: 10.3389/fimmu.2021.651739
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology of Acute Kidney Injury in Severe Malaria

Abstract: Acute kidney injury (AKI) is a common feature of severe malaria, and an independent risk factor for death. Previous research has suggested that an overactivation of the host inflammatory response is at least partly involved in mediating the kidney damage observed inP. falciparumpatients with AKI, however the exact pathophysiology of AKI in severe malaria remains unknown. The purpose of this mini-review is to describe how different aspects of malaria pathology, including parasite sequestration, microvascular ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 59 publications
1
32
0
2
Order By: Relevance
“…In this process, the EG is likely eroded, promoting coagulation, leukocyte adhesion, and loss of endothelial barrier function that culminates in cerebral edema [119] , [120] , [121] . Acute kidney injury is also common with P. falciparum through microvascular occlusion, local inflammation, and EG erosion [122] , [123] , resulting in filtration and tubular absorption defects [124] .…”
Section: The Endothelial Glycocalyx In Specific Pediatric Critical Il...mentioning
confidence: 99%
“…In this process, the EG is likely eroded, promoting coagulation, leukocyte adhesion, and loss of endothelial barrier function that culminates in cerebral edema [119] , [120] , [121] . Acute kidney injury is also common with P. falciparum through microvascular occlusion, local inflammation, and EG erosion [122] , [123] , resulting in filtration and tubular absorption defects [124] .…”
Section: The Endothelial Glycocalyx In Specific Pediatric Critical Il...mentioning
confidence: 99%
“…Previously, it has been proposed that parasite sequestration in the kidney may play a role in the pathogenesis of AKI in malaria ( Katsoulis et al., 2021 ). In post-mortem studies, sequestration of P. falciparum parasites was higher in glomerular and peritubular capillaries of patients with AKI compared to malaria patients without AKI ( Nguansangiam et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parasite sequestration, which is the binding of infected red blood cells (iRBCs) to endothelial cells (ECs), has been proposed as a potential contributor to AKI pathogenesis in malaria ( Katsoulis et al., 2021 ). Post-mortem studies observed parasite sequestration of P. falciparum in glomerular and peritubular capillaries in adults and children with MAKI ( Nguansangiam et al., 2007 ; Milner et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite multiple Plasmodium species being reported to lead to kidney pathology, the relationship between kidney immune complex deposition and kidney pathology has only been reported in P. malariae malaria (29). This suggest that other non-autoantibody immune factors are needed in addition to promote kidney pathology in other human malarias underscoring the complexity of this phenomena (30). Lastly, there have also been several studies reporting autoantibodies against brain-associated antigens in patients suffering from P. falciparum cerebral malaria, but their pathogenic relevance remains to be determined (25).…”
Section: Pathological Role Of Autoantibodies During Malarial Anemia A...mentioning
confidence: 99%